PENERAPAN PENCORETAN (ROYA) JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN ANTARA PERSEROAN TERBATAS PEGADAIAN (PERSERO) DAN NASABAH DI KOTA PEKANBARU - LOLA VITA LOKA PURBA; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Economic development requires substantial funds and to meet the needs of the fund established financing institutions that can help such large funding requirements. one of the financial institutions is that channeling funds through the pawn shops pawn system and then to help the government program to help small and medium enterprises, the pawnshops accept collateral with fidusia and based one of which is a Limited Liability Company Pawn (Persero).Fiduciary guarantee the transfer of ownership of an object on the basis of trust with the provision that transferred ownership rights object is retained by the owner, and the fiduciary must register with the registration office fiduciary and Mortgage Company Limited (Persero) branch of Pekanbaru City always register but enactment law also regulates the deletion fiduciary after customers paid off debt and Pawn party never do that. the purpose of this thesis was to determine (1) The write-off (Roya) fiduciary between Mortgage Company Limited (Persero) and customers in the city of Pekanbaru (2) the efforts made Pawn Company Limited (Persero) in addressing the problem of deletion (Roya).This study uses a kind of sociological research the correlation between law and society. This study also uses primary data, secondary data and data tertiary. From the research we concluded that in the application of the write-off (Roya) fiduciary in the financing agreement between the Company Limited Pawn (Persero) and customers in the city of Pekanbaru is not in accordance with the legislation in force despite all fiduciary registered but after debt clients paid off never do deletion (roya). In an effort to overcome the problem of the party Roya Pawn Company Limited (Persero) did not make any effort caused during this time they have never had a problem with not doing it and remain that they can re-enroll the same object even if the certificate has not been done previously deletion (Roya).Keywords: Application - Fiduciary - Roya